Chesapeake Bay: Inner Harbor - Book 3 - Roberts, Nora (New York : Jove Books, 1999)
In the conclusion to the trilogy beginning with "Sea Swept", Philip Quinn's bond to his adopted brother, Seth, is threatened by a young woman with a troubling secret.
Sequel to: Rising tides.